Preserving connectivity under climate and land-use change: No one-size-fits-all approach for focal species in similar habitats - Costanza, Jennifer K.; Watling, James; Sutherland, Ron; Belyea, Curtis; Dilkina, Bistra; Cayton, Heather; Bucklin, David; Romañach, Stephanie S.; Haddad, Nick M. (Biological conservation, 2020)
Habitat connectivity is essential for maintaining populations of wildlife species, especially as climate changes. Knowledge about the fate of existing habitat networks in a changing climate and in light of land-use change is critical for determining which types of conservation actions must be taken to maintain those networks. However, information is lacking about how multiple focal species that use similar habitats overlap in the degree and geographic patterns of threats to linkages among currently suitable habitat patches. We sought to address that gap. We assessed climate change threat to existing linkages in the southeastern United States for three wildlife species that use similar habitats but differ in the degree to which their ranges are limited by climate, habitat specificity, and dispersal ability. Linkages for the specialist species (timber rattlesnake), whose range is climate-restricted, were more likely to serve as climate change refugia – that is, they were more likely to be climate-stable – by the middle of the 21st century. This contrasts with the two more generalist species (Rafinesque's big-eared bat and American black bear), whose linkages were threatened by climate change and thus required adaptation measures. Further incorporation of projected land-use change and current protection status for important linkages narrows down our recommended conservation actions for each species. Our results highlight the surprising ways in which even species that use similar habitats will experience differences in the degree and geographic patterns of threats to connectivity. Taking action before these projected changes occur will be critical for successful conservation.